Recruitment to higher specialty training in anaesthesia in the UK during the COVID‐19 pandemic: a national survey. (21st January 2022) - Subramaniam, J.; Durrant, F.; Edwardson, S.; El‐Ghazali, S.; Holt, C.; McCrossan, R.; Pramanik, I.; Wong, D. J. N.
Summary: There were more applications for higher specialty training posts in anaesthesia in the UK starting in August 2021 than in previous years, with approximately two‐thirds being unsuccessful. We surveyed applicants to investigate their experience of the recruitment process (response rate 536/1056; 51%). Approximately 61% of respondents were not offered ST3 posts (n = 326). We enquired about their career plans for the next 12–24 months. Most respondents (79%) intended to take up a post equivalent to a third year of core training or a clinical fellow post from August 2021. Other options considered included: pursuing work abroad (17%); embarking on career breaks (16%); taking up higher training posts in intensive care medicine (15%); and permanently leaving medicine (9%). Nine per cent of respondents also expressed plans to pursue training in another medical specialty. Some expressed an intention to pursue further education or research (10%). A large proportion (42%) expressed a lack of confidence in being able to achieve the training requirements to later apply for a higher training post. The majority reported not feeling confident in achieving specialist registration in anaesthesia in the future without a training number (75%), and noted disruption to their wider life plans from the impending time out of training (78%). Sentiment analysis of free‐text responses indicated generally negative sentiment about the recruitment process. Themes elicited included: feeling the recruitment process was unfair; burnout and negative impact on well‐being; difficulties in making life plans; and feeling undervalued and abandoned. These results suggest that junior anaesthetic doctors in the UK negatively perceived postgraduate training structures and changes to the postgraduate curriculum and experienced difficulties in securing higher training.